THE BURNOUT EPIDEMIC: AN HR CRISIS AND WHAT TO DO ABOUT IT - Dahlina Nopilawati; Tibrani; Lukmanul Hakim (RADJA PUBLIKA, 2026)
This article addresses the pervasive and costly organizational crisis of employee burnout. The background establishes burnout as a syndrome of exhaustion, cynicism, and reduced efficacy, increasingly prevalent in modern workplaces. The objective is to argue that HR must lead a systemic, strategic intervention, moving beyond individual resilience programs to address root causes. The methodology synthesizes the seminal Job Demands-Resources model and Christina Maslach’s Six Mismatches framework with contemporary research on organizational psychology and work design. The results present a diagnostic audit based on the six mismatches and a multi-tiered intervention strategy targeting organizational systems, managerial practices, and cultural norms. The discussion posits that burnout is a critical failure of work design, not a personal failing, and that sustainable performance is only possible through humane systems. The conclusion asserts that transforming the approach to burnout from a wellness issue to a strategic priority is essential for ethical leadership and long-term competitive advantage.